Discourse and identity formation : parliamentary debates in Bahrain - Alkooheji, Lamya; Sinha, Chitra (Discourse approaches to politics, society, and culture, 2017)
The book explores eleven debates held at the Bahraini Council of Representatives (or the Parliament) over 2007-2010, to comprehend how parliamentary discourse contributes towards identity formation within Bahraini society.